Combinations of ruminally degradable and escape protein for implanted finishing steers - Milton, C.T.; Brandt, Robert T., Jr.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-four crossbred medium framed steers (738 lb) were used to compare urea and soybean meal as basal supplemental nitrogen sources and sources of high (blood meal:corn gluten meal; BMCG) or low (soybean meal; SBM) ruminal escape proteins as additional protein supplementation. Basal diets were formulated to contain 1 0.8% crude protein (CP) and were supplemented with either urea or SBM (.91% and 5.55% of DM, respectively). An additional 2 percentage units of CP were either provided or not provided as SBM or as a 50:50 combination (protein basis) of BMCG. Steers were implanted with Revalor-S® and fed experimental diets for 113 days. Steers fed urea diets consumed 3.9% more feed than those fed SBM as the basal N source. Average daily gain was unaffected by treatment. Soybean meal improved feed efficiency 3.8% compared to urea as a basal nitrogen source. Supplying additional CP from SBM increased feed efficiency 4.4% compared to BMCG. Hot carcass weight and dressing percentage were not affected by treatment. Supplementing basal diets with 2 percentage units of CP increased percentage of carcasses grading choice, KPH fat, and yield grade. High dry matter intakes resulted in metabolizable protein intakes above the predicted requirements (760 g/d) for steers in this experiment, which may have precluded a response to supplemental protein.
Keywords: Beef; Degradable protein; Escape protein; Finishing steers; Performance